Tumor biology experimental course design based on the integration of molecular biology and metabolomics - Zhu, Xinliang; Tang, Ting (Cogent education, 2024)
In recent years, single-subject experimental courses have not been able to meet the demands of the comprehensive development of life sciences. This study is based on two fundamental disciplines, molecular biology and metabolomics, with the analysis and intervention of tumor-related genes as the starting point. A comprehensive experimental course has been set up to analyze oncological genetic abnormal induced molecular signature and metabolome feature alterations through in vitro and in vivo experimental validations. This newly designed course combines guide theories and practical instructions. Through database screening, in vitro research and in vivo research, student's research interest and knowledge reserves are greatly enhanced and a foundation is laid for further scientific research in the future.